TANGGUNG JAWAB HUKUM ATAS PERUSAHAAN FARMASI TERHADAP BEREDARNYA OBAT YANG MENGANDUNG BAHAN BERBAHAYA - Siti Nurholisoh; Rani Apriani (Fakultas Hukum Universitas Islam Syekh Yusuf, 2022)
The rampant circulation of dangerous medicinal substances in Indonesia is concerned with the lack of legal awareness of business actors who are trying to achieve maximum profit by ignoring the enormous negative impact on the wider community. Acts that violate these norms must be held accountable. So that this research is considered important to find out how the legal responsibility of pharmaceutical companies for the circulation of drugs containing hazardous materials. This research method uses a normative juridical approach, the research specification uses an analytical description. The types and techniques of data collection in this study were carried out by literature study methods and data analysis methods used in this study using qualitative data analysis. The legality of pharmaceutical companies as business actors is very important. In addition, in producing and/or distributing pharmaceutical preparations such as drugs, medicinal ingredients, traditional medicines and cosmetics, they must meet standards and not violate the law. Keywords: Responsibility; Pharmaceutical Business; Consumer protection.